Experimental study on the compressive strength and mechanical properties of gravelly red sandstone soil under freeze-thaw cycles - Benson, Ezekiel; Cheng, Peng; Chao, Li (Frontiers in Materials, 2025)
Gravelly soils, characterized by a distinctive combination of coarse gravel aggregates and fine soil matrix, are widely distributed and play a crucial role in geotechnical engineering. This study investigates the mechanical behavior of gravelly soil subjected to simulated freeze-thaw (F-T) cycles using triaxial compressive strength tests. The long-term deviatoric stress response of specimens with varying gravel content and initial water content was analyzed under three distinct effective confining pressures (100, 200, and 300 kPa) across different F-T cycles. The results indicate that compressive strength is significantly influenced by gravel content, initial water content, and confining pressure. Notably, the rate of increase in deviatoric stress does not exhibit a proportional rise under confining pressures of 200 kPa and 300 kPa after 40 F-T cycles. However, a direct correlation is observed between deviatoric stress and increasing confining pressure (100, 200, and 300 kPa) over 2-, 4-, and 6-day intervals, this effect is more pronounced at higher confining pressures. The deviatoric stress peaks at different strain thresholds depending on the applied confining pressure; furthermore, no evident strain-softening behavior is observed across the tested conditions. These findings suggests that higher confining pressure inhibits particle displacement and interlocking failure, thereby reducing both the void ratio and axial strain within the soil matrix. Overall, these insights enhance our understanding of the complex interactions among gravel content, water content, confining pressure, and freeze-thaw effects, contributing to the understanding of the compressive strength evolution in gravelly soils under cyclic environmental loading.